Refractory vasculitic ulcer of the toe in adolescent suffering from Systemic Lupus Erythematosus treated successfully with hyperbaric oxygen therapy - Mauro Angela; Di Meglio Milena; Duilio Carlo; Mellos Antonio; Olivieri Alma N; Perrone Laura (BMC, 2010)
Abstract Skin ulcers are a dangerous and uncommon complication of vasculitis. We describe the case of a teenager suffering from Systemic Lupus Erythematosus with digital ulcer resistant to conventional therapy, treated successfully with Hyperbaric Oxygen Therapy. The application of hyperbaric oxygen, which is used for the treatment of ischemic ulcers, is an effective and safe therapeutic option in patients with ischemic vasculitic ulcers in combination with immunosuppressive drugs. Further studies are needed to evaluate its role as primary therapy for this group of patients.